The Cause and Effect of Delay in LRT3 Depot Construction Project - Abd Aziz, Muhammmad Khairunnas; Prasetijo, TD DR Joewono (Progress in Engineering Application and Technology, 2022)
The construction industry in Malaysia is one of the most significant contributors to economic growth and jobs. However, the increased rate of construction delivery delays is a key worry for the construction sector. In the worst-case scenarios, projects were postponed for more than a year after the contract time had passed. Delay in construction projects is defined as an increase in the amount of time it takes to complete the project. In other terms, a delay occurs when a project is not completed within the agreed-upon timeframe and budget. When projects are delayed, it has a negative impact on several parties, including the developer, contractor, consultant, and client. This research will look at the causes of project delays, as well as the consequences of project delays, in order to make recommendations on how to avoid or minimise project delays. The information was gathered from respondents who worked on the LRT3 Depot Construction and had previous experience of working on a mega construction project.